Nineteenth‐Century Tides in the Gulf of Maine and Implications for Secular Trends. Issue 10 (23rd October 2019) - Ray, R. D.; Talke, S. A.
Abstract: Since the early twentieth century, the amplitudes of tidal constituents in the Gulf of Maine and Bay of Fundy display clear secular trends that are among the largest anywhere observed for a regional body of water. The M2 amplitude at Eastport, Maine, increased at a rate of 14.1 ± 1.2 cm per century until it temporarily dropped during 1980–1990, apparently in response to changes in the wider North Atlantic. Annual tidal analyses indicate M2 reached an all‐time high amplitude last year (2018). Here we report new estimates of tides derived from nineteenth century water‐level measurements found in the U.S. National Archives. Results from Eastport, Portland, and Pulpit Harbor (tied to Bar Harbor) do not follow the twentieth century trends and indicate that the Gulf of Maine tide changes commenced sometime in the late nineteenth or early twentieth centuries, coincident with a transition to modern rates of sea‐level rise as observed at Boston and Portland. General agreement is that sea level rise alone is insufficient to cause the twentieth‐century tide changes. A role for ocean stratification is suggested by the long‐term warming of Gulf of Maine waters; archival water temperatures at Boston, Portland, and Eastport show increases of ∼2 °C since the 1880s. In addition, a changing seasonal dependence in M2 amplitudes is reflected in a changing seasonal dependence in water temperatures. The observations suggest that models seeking to reproduce Gulf of Maine tides must consider both sea level rise and long‐term changes in stratification. Key Points: Nineteenth‐century water‐level measurements have been recovered for Eastport, Portland, and Pulpit Harbor, Maine Large twentieth century trends in tidal amplitudes do not extend back into the nineteenth century Tidal trends are coincident with modern rates of sea level rise at Boston and Portland but changing stratification is likely important